Early oral tongue cancer initially managed with surgery alone: Treatment of recurrence. Issue 4 (1st December 2016) - Liu, Jeffrey C.; Sopka, Dennis S.; Mehra, Ranee; Lango, Miriam N.; Fundakowski, Christopher; Ridge, John A.; Galloway, Thomas J.
Abstract : Objective: To report T1‐2N0 tongue cancer recurrences initially treated with surgery alone. Methods: Between 1990 and 2010, 27 patients at tertiary hospital referral center institution were treated with curative intent for locoregional recurrence after initial glossectomy with or without neck dissection for T1‐2N0 tongue cancer. None had received adjuvant postoperative radiation as a component of the original treatment. Results: Median time to locoregional recurrence was 12 months (range 5–39 months) and 78% of failures occurred in the first 2 years. Most treatment failures were local (63%). Salvage strategy was risk‐adapted by individual patient. The 5‐year disease specific survival (DSS) was 61%. Patients with local recurrences alone fared significantly better than those with regional recurrences (5‐yr DSS: 86% vs . 22%, P  = 0.0018). Local recurrences were usually treated by surgery alone, while regional recurrences were more commonly treated with combined modality treatment ( P  = 0.005). Conclusions: Recurrence of early stage oral tongue cancer can be successfully salvaged in a majority of cases. Patients developing regional recurrence have significantly worse prognosis than those with local failures.